Relasi Kuasa Nelayan Pemilik Kapal dengan ABK di Pelabuhan Karangantu, Serang Banten - Putri, Sabrina Mustika; Haryono, Haryono; Setiawan, Rizki (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This study examines the complex social structure and power relationships among fishermen in Karangantu Harbor. The focus of this research highlights the interaction between independent ship owners and ship crew members (ABK). The social structure is characterized by three distinct strata: land-based investors, boat-owning fishermen, and crew members, with crew members heavily dependent on others for their livelihood. Using a descriptive qualitative case study approach, this research examines how ownership of assets such as boats and fishing equipment not only facilitates production but also establishes social status and economic influence within a community. Findings reveal a network of economic dependencies and reduced bargaining power for crew members, emphasizing the unequal power dynamics prevalent in the industry. Peter Blau's theoretical framework provides a lens for interpreting these relationships, highlighting the subtle interplay of power and social exchange in maritime socioeconomic contexts.